Neuronal Migration Disorders in Children; A Case Series highlighting importance of Neuroimaging in diagnosing Epilepsy - Patil, Smita; Amit Vatkar; Vijayan, Vineetha (Nepal Journal of Neuroscience, 2024)
Background: Neuronal migration disorders comprise a heterogeneous group of neurological conditions caused by abnormal neuronal positioning during brain development. We aimed to study the clinical profile, neuroimaging features, genetics, and treatment of neuronal migration disorders. Methods: This was a retrospective case series of 15 pediatric patients diagnosed with neuronal migration disorders at a tertiary care hospital over a 5 year period. Detailed clinical evaluation, neuroimaging, EEG, and genetic analysis were performed. Results: Global developmental delay and epilepsy were the most common presenting features. Neuroimaging revealed spectrum of cortical dysgenesis including pachygyria, polymicrogyria, lissencephaly, heterotopia, and schizencephaly, predominantly involving fronto-parietal regions. MRI coupled with clinical findings enabled definitive diagnosis. Genetic analysis identified mutations in PAFAH1B1, ADGRG1, DHDDS, TMTC3, and other genes. Anti-seizure medications like valproate, levetiracetam, and clobazam were the mainstay of therapy. Non-pharmacological interventions including physiotherapy, occupational therapy, and speech therapy were employed. Conclusion: This study demonstrates the diverse clinical, genetic, and radiological spectrum of neuronal migration disorders. Comprehensive evaluation along with neuroimaging and genetic analysis enables accurate diagnosis and guides management. A multimodal approach is required focusing on seizures, neurodevelopmental disabilities, and improving quality of life.